Reactive Oxygen Species (ROS) Are Not a Key Determinant for Zika Virus-Induced Apoptosis in SH-SY5Y Neuroblastoma Cells - Leila Rodrigues de Mendonça-Vieira; Conceição Elidianne Aníbal-Silva; Armando Menezes-Neto; Elisa de Almeida Neves Azevedo; Nágela Ghabdan Zanluqui; Jean Pierre Schatzmann Peron; Rafael Freitas de Oliveira Franca (Viruses, 2021)
Introduction: ZIKV is a highly neurotropic virus that can cause the death of infected neuroprogenitor cells through mitochondrial damage and intrinsic apoptotic signaling. In this context, the role of reactive oxygen species (ROS) in neuronal cell death caused by ZIKV still remains elusive. Objective: We aimed at evaluating the role of these cellular components in the death of human undifferentiated neuroblastoma cell line infected with ZIKV. Results: ZIKV infection resulted in the extensive death of SH-SY5Y cells with the upregulation of several genes involved in survival and apoptotic responses as well as the colocalization of mitochondrial staining with ZIKV Envelope (E) protein. Notably, levels of intracellular reactive oxygen species (ROS) were not altered during ZIKV infection in undifferentiated SH-SY5Y cells, and consistent with these results, the treatment of infected cells with the widely studied ROS scavenger N-acetylcysteine (NAC) did not prevent cell death in these cells. Conclusion: Altogether, our results suggest that excessive ROS production is not the main trigger of SH-SY5Y cells death in ZIKV infection.